Mechanism of Action of Nicotiflorin from Tricyrtis maculata in the Treatment of Acute Myocardial Infarction: From Network Pharmacology to Experimental Pharmacology - Yu S; Guo Q; Jia T; Zhang X; Guo D; Jia Y; Li J; Sun J (Dove Medical Press, 2021)
Shangshang Yu,1,* Qi Guo,1,* Tianqian Jia,2,* Xiaofei Zhang,1 Dongyan Guo,1 Yanzhuo Jia,1 Jia Li,1 Jing Sun1 1Shaanxi University of Chinese Medicine, Xianyang, People’s Republic of China; 2Haojing College of Shaanxi University of Science & Technology, Shaanxi, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Sun Tel +86 029-38184958Email 3332606446@qq.comPurpose: Acute myocardial infarction (AMI) is a cardiovascular disease with a high fatality rate. In this study, we combined network pharmacology and experimental pharmacology and discovered the potential mechanism of action and the active ingredients of the lily, Tricyrtis maculata was discovered. The monomer compound with stronger activity was discovered through in vitro cell experiments.Methods: Forty known compounds were isolated from T. maculata. Using TCMSP, Swiss Target Prediction, metaTarFisher, GeneCards and OMIM databases, targets of drug compositions and AMI-related genes were obtained, and the differential expression genes between AMI and normal tissues were extracted through the GEO database. Then, through an online mapping tool, the intersection genes were obtained to predict the possible effective components of T. maculata that can be used to treat AMI. The top five targets were selected for molecular docking via the protein–protein interaction (PPI) network to verify the binding activity between key compounds and target proteins. GO and KEGG enrichment analyses of the intersection genes were carried out with the program R to further screen key genes and effective compositions. On this basis, the compound with more optimal activity was screened and validated in vitro.Results: In this study, 40 known monomer components were selected, and 1112 predicted genes, 1655 disease genes, 1425 differentially expressed genes, 1206 GO functions and 127 KEGG pathways were obtained. The results of molecular docking showed that the binding of MMP9 with drug components is stable. Through the comprehensive research of network pharmacology and experimental pharmacology, it was shown that T. maculata intervenes in the process of AMI through multicomponent, multitarget, and multichannel synergistic effects. It is speculated that the anti-AMI effect may be related to the regulation of the Akt/FoxO/BCl signaling pathway. Cellular experiments showed that nicotiflorin has satisfactory anti-inflammatory activity and endothelial protection and can reduce the release of nitric oxide (NO), an inflammatory medium after endothelial cell damage.Conclusion: This study reveals the therapeutic effect and relative mechanism of extract of T. maculata extract on AMI. Analysis revealed that nicotiflorin from T. maculata is a compound with satisfactory anti-inflammatory activity and endothelial protection, which provides a new direction and treatment basis for further experimental exploration and clinical treatment.Keywords: Tricyrtis maculata, nicotiflorin, network pharmacology, experimental pharmacology, GEO data mining